Emergency response and preparedness assessment among migrant construction workers - Hian, Heng Chun; Mohd Najib, Yacob (2022)
Emergency can result in various hazards to employers, workers, and other persons at scene. Preparing before emergency can make sure that employees have the knowledge, equipment, and ability to protect themselves. However, the status of emergency response and preparedness among migrant construction workers is unclear in Malaysia. This study aims to assess the emergency response and preparedness among migrant workers from the related implementations, attitudes, and barriers. A quantitative survey method was used to collect the data through questionnaires in a construction company in Johor. A total of 106 respondents (18 from management position, 88 from general position) were participated in the study. The implementations in worker participation involving activities and worker representative were identified as low level. However, the attitude towards emergency response and preparedness among migrant construction workers were generally positive. Lastly, the language, behaviour and management were all barriers in implementing emergency response and preparedness